2019
DOI: 10.1002/app.48001
|View full text |Cite
|
Sign up to set email alerts
|

Reinforced thin‐film composite nanofiltration membranes: Fabrication, characterization, and performance testing

Abstract: Hollow‐fiber (HF) membranes have the advantage of a higher packing density compared to flat‐sheet and spiral‐wound configurations. However, the low pressure tolerance of HF membranes limits their applications in nanofiltration (NF). In this study, reinforced thin‐film composite (r‐TFC) HF NF membranes were fabricated and evaluated in tests with water containing different salts and organic matter. Reinforced polysulfone ultrafiltration membranes were used as a support for a polyamide layer prepared from piperaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The hydrophilicity of the membrane increased by enhancement of the crosslinking degree of the polyamide layer and the TMC reaction time. Turken et al [51] reported the higher specific permeate flux in higher TMC reaction times for reinforced-TFC-NF membranes. The hydrophilicity of the membrane enhanced when the reaction time of TMC increased.…”
Section: Effect Of Soaking and Reaction Time In Tfc-bhfm Preparationmentioning
confidence: 99%
See 4 more Smart Citations
“…The hydrophilicity of the membrane increased by enhancement of the crosslinking degree of the polyamide layer and the TMC reaction time. Turken et al [51] reported the higher specific permeate flux in higher TMC reaction times for reinforced-TFC-NF membranes. The hydrophilicity of the membrane enhanced when the reaction time of TMC increased.…”
Section: Effect Of Soaking and Reaction Time In Tfc-bhfm Preparationmentioning
confidence: 99%
“…Reaction time is a crucial factor in interfacial polymerization that affects the structure of the coating layer and specifies the extent of polymerization between the monomers [53]. Turken et al [51] fabricated reinforced TFC-HF NF membranes. They selected the reinforced PSf ultrafiltration as a support and polyamide layer as a selective layer that was prepared from trimesoyl chloride (organic phases) and piperazine (aqueous phases) monomers.…”
Section: Effect Of Soaking and Reaction Time In Tfc-bhfm Preparationmentioning
confidence: 99%
See 3 more Smart Citations